Subject-figurative structures in Tatar and Tuvan poetry of the 1970s — 1990s - Amineva, Venera R.; Mizhit, Lyudmila S. (The New Research of Tuva, 2021)
The article identifies several types of subject-figurative situations in Tatar and Tuvan poetry, taking the works of Tatar and Tuvan poets (I. Yuzeyev, R. Akhmetzyanov, R. Gatash, A. Uerzhaa, A. Darzhay, E. Mizhit, N. Kuular) for its sources. These literary situations are investigated as manifestations of the national identity in a literary text, and as a cultural space that reflects similar trends in the historical and literary process. The paper relies on systemic-structural, comparative, and hermeneutic methods of research. The authors examine the main types of subject-figurative situations in the work of poets which reflect the ways of self-determination of the lyrical subject. They conclude that I. Yuzeev’s and A. Uerzhaa’s lyrical protagonist seek to take a position of self-reflective “outsidedness” in relation to himself, which brings the subject-figurative integrity of their work to the meta-image level. R. Akhmetzyanov’s and A. Darzhay’s lyrical subject turns out to be probabilistically plural, not coinciding with itself. At the same time, it syncretically combines two types of consciousness - folk-mythological and individualized. The study postulates that the specificity of the subject-figurative integrity in Tatar and Tuvan poetry manifests itself in the relationship between the “I” and what may be termed ‘super-subjects’, which personify the active volitional power with its supra-personal “outsidedness” influencing the lyrical situation and its heroes. Elements of life, nature, love, and creativity acquire full agency in poems by R. Akhmetzyanov, E. Mizhit, R. Gatash, A. Uerzhaa, and N. Kuular. Vital and creative position of the “lyrical protagonist” and “author” is revealed in this dialogical appeal to the super-subjects which transcend individual consciousness. Mythopoetic “languages” of cumulation and parallelism play a decisive role in setting the types of abovementioned subject-figurative structures in Tatar and Tuvan poetry of the 1970s-1990s. They interact with the conditionally poetic language that indicates the relativity of the existential plane of the poetic imagery and sets its limits in each specific case. The outcomes of the study can be important for developing the historical poetics of Tatar and Tuvan literature of the latter half of the 20th century.